2010
DOI: 10.4049/jimmunol.0902166
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Epitopes Induce High-Titer Humoral Immune Response in Patients with Cancer

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This phenomenon was suggested to aid immune maturation and the formation of vaccines to enable the killing of tumor cells. It was shown that ingestion of blebs by mouse-derived dendritic cells induced their maturation and subsequent Th17 cell activation when co-cultured with splenocytes in vitro [ 138 , 139 ], as well as in mice in vivo [ 140 ]. Ruben et al [ 116 ] showed that blebs were generated from mitoxantrone-treated apoptotic HL60 cells (the human HLA-A2-negative AML cell line), which contain chromatin and endoplasmic reticulum.…”
Section: Role Of Blebbing In Cellular Locomotionmentioning
confidence: 99%
“…This phenomenon was suggested to aid immune maturation and the formation of vaccines to enable the killing of tumor cells. It was shown that ingestion of blebs by mouse-derived dendritic cells induced their maturation and subsequent Th17 cell activation when co-cultured with splenocytes in vitro [ 138 , 139 ], as well as in mice in vivo [ 140 ]. Ruben et al [ 116 ] showed that blebs were generated from mitoxantrone-treated apoptotic HL60 cells (the human HLA-A2-negative AML cell line), which contain chromatin and endoplasmic reticulum.…”
Section: Role Of Blebbing In Cellular Locomotionmentioning
confidence: 99%
“…Some of the most common host-derived antibodies target Her2, p53, MUC1, and endostatin [53], and to date over 250 breast cancer antigens have been identified [35]. Non-identified antigens, also known as “cryptic epitopes”, which were discovered by sequencing V(D)J regions and not finding a matched antigen, have also been documented [51,54] and are specific for binding to breast cancer cells and not normal tissue [54]. Together, these data demonstrate that active, humoral immune responses do occur in at least some breast cancer patients although, these processes are not solely B cell dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Serum antibodies to tumor-specific antigens have been documented in pancreatic, cervical, gastric and ovarian cancers [35,39,52,54,97]. Presence of antibodies to MUC1, a common tumor antigen, showed improved survival for ovarian, gastric, lung and pancreatic cancers [97].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of a model self-antigen, it was demonstrated that exposure of antigen presenting cells to the cytokine IL-6 led to the processing and presentation of cryptic determinants of an antigen [ 44 ]. Display of cryptic determinants has been described as a cornerstone for activation of self reactive T cells in autoimmunity [ 45 ] and also been documented to occur in anti-tumor immunity [ 46 ]. Cryptic epitopes of self-antigens highly expressed by tumors have been demonstrated to be pivotal targets of therapy that result from qualitative and quantitative differences in antigen handling by APC [ 46 ].…”
Section: Immunological Rationale For Vaccination Strategies Targetingmentioning
confidence: 99%
“…Display of cryptic determinants has been described as a cornerstone for activation of self reactive T cells in autoimmunity [ 45 ] and also been documented to occur in anti-tumor immunity [ 46 ]. Cryptic epitopes of self-antigens highly expressed by tumors have been demonstrated to be pivotal targets of therapy that result from qualitative and quantitative differences in antigen handling by APC [ 46 ]. IL-6 itself has a prominent role in tumor angiogenesis, upregulating VEGF expression [ 47 ].…”
Section: Immunological Rationale For Vaccination Strategies Targetingmentioning
confidence: 99%